Evaluation of Dimensional Accuracy and Feasibility of an in House Desktop Printer for Preoperative Planning and Precontouring of Implants for Craniomaxillofacial Surgery - Shahana Parveen; Dinesh Kumar; Mausumi Iqbal; Ayushi Mishra; Yogesh Garg; Shailesh Jain (Journal of Pharmacy and Bioallied Sciences)
Background: 3D printing soon after its inception has spread globally as a useful tool in preoperative planning. Thus, this study aims to evaluate the accuracy and efficacy of the 3D printed models in preoperative surgical planning and prebending of implant adaptation for craniomaxillofacial surgery. Methods: A prospective study including 10 patients requiring complex maxillofacial management. A preoperative CBCT/CT scan of the patient was obtained in DICOM format was obtained, and data were converted to STL format by using Mimics software. Time taken for the surgery and amount of blood loss were also recorded. All patients were followed up at intervals of 1 week, 1 month, and 3 months for assessing facial symmetry. Results: Average time and blood loss during the operative procedure that was observed were 217.5 min and 405 mL, respectively. Evaluation of facial symmetry showed good facial symmetry (90%) and showed fair facial symmetry (10%), and there was the restoration of facial symmetry to a preoperative premorbid state. Conclusions: The present study suggests the advantages and outcomes of 3D printing technology surpass the limitations and thus recommends the use of a 3D printed model for preoperative planning for minor as well as major and complex craniomaxillofacial surgery.